Wild babies - Simon, Seymour (New York : HarperCollins, 1997)
Describes the various parenting techniques of different types of wild animals and provides a close look at the behavior and characteristics of their offspring.
Wilson's Children
Elem. School Library Collection
School Library Journal
5.5
K-3
Keywords: Animals -- Infancy -- Juvenile literature; Parental behavior in animals -- Juvenile literature; Animals -- Infancy; Parental behavior in animals; Animal babies; Parenting in animals; Animal behavior